Agroecological techniques: adoption of safe and sustainable agricultural practices among the smallholder farmers in Africa - Akanmu, Akinlolu Olalekan; Akol, Anne Margaret; Ndolo, Dennis Obonyo; Kutu, Funso Raphael; Babalola, Olubukola Oluranti (Frontiers in Sustainable Food Systems, 2023)
Attaining sufficiency in food supply to support a growing population without compromising ecosystem functioning remains a top agenda of researchers and agricultural stakeholders. Agroecological farming approaches are effective techniques that ensure sustainable food production even in adverse situations. Population growth has been forecasted to reach over 9.1 billion by 2050 outpacing food production. However, cereals and grain legumes are strategic to achieving the United Nations Sustainable Development Goal of zero hunger by 2030 (SDG 2), ending extreme poverty (SDG 1), and mitigating the climate change effect (SDG 13). There remains an urgent need to embrace more sustainable measures to increase food production for the growing population. This review explores the role of agroecology which employs a transdisciplinary approach to sustainable agricultural practices to improve the resilience of farming systems by increasing diversification through poly-cropping, agroforestry, use of local varieties, and integrated crop and livestock systems. Furthermore, the agroecological farming approach minimizes water use, lowers pollution levels on the farm, and ensures economic profitability for the farmers. Thus, application of agroecology techniques among the smallholder farmers is strategic to ensuring food security.